Simulation analysis of different strength levels of EOG signals - Mohd Noor, Nurul Muthmainnah; Ahmad, Salmiah (2012)
This paper described the signal from the eye muscles that is called electrooculogram which is generated at different eye movement’s directions and levels. The eye movement signal data is captured by using Al/AgCl electrodes and passed through the g.USBamp from G.TEC Medical Engineering GMBH eye movement data collection. The eye movement data is passed to the Matlab/Simulink software for data analysis. The electrooculography (EOG) signals are obtained from four (4) different places around eye (right, left, up, and down) with different level of strengths will produce different strength of EOG signal. The EOG data obtained could be very helpful in many applications such as in the field of rehabilitation for example as a communication tool to operate a wheelchair among tetraplegia.